Вынужденные осесимметричные колебания и разогрев термовязкоупругих цилиндрических оболочек с пьезоактуаторами - Киричок, И.Ф.; Карнаухова, Т.В. (Прикладная механика, 2010)
The coupled problem is solved on forced axisymmetric vibrations and dissipative heating of electrothermoviscoelastic cylindrical shells with piezoceramic actuators under monoharmonic electromechanical loading. The temperature dependence of complex characteristics of passive and piezoactive materials is taken into account. A coupled problem of electrothermomechanics is solved by the step-by-step in time integration with use on each iteration of the method of discrete orthogonalization for integration of equations of mechanics and the explicit scheme of the finite difference method for solving the heat conductivity equations. An effect of conditions of mechanical fastening the shell faces, geometrical sizes of piezoactuator and dissipative heating temperature on active damping of forced vibrations of cylindrical shell and actuator indication is studied for the case of uniform transverse monoharmonic pressure.